Cell-Free Tumor DNA (ctDNA) Utility in Detection of Original Sensitizing and Resistant EGFR Mutations in Non-Small Cell Lung Cancer (NSCLC) - Jason S. Agulnik; Andreas I. Papadakis; Carmela Pepe; Lama Sakr; David Small; Hangjun Wang; Goulnar Kasymjanova; Alan Spatz; Victor Cohen (Current Oncology, 2022)
Background: Recent studies have demonstrated the utility of cell-free tumor DNA (ctDNA) from plasma as an alternative source of genomic material for detection of sensitizing and resistance mutations in NSCLC. We hypothesized that the plasma level of ctDNA is an effective biomarker to provide a non-invasive and thus a less risky method to determine new resistance mutations and to monitor response to treatment and tumor progression in lung cancer patients. Methods: This prospective cohort study was approved and conducted at the Peter Brojde Lung Cancer Centre, Montreal. Blood was collected in STRECK tubes at four time points. DNA was extracted from plasma, and ctDNA was analyzed for the presence of mutations in the EGFR gene using the COBAS® EGFR v2 qPCR (Roche) test. Results: Overall, 75 pts were enrolled in the study. In total, 23 pts were TKI-naïve, and 52 were already receiving first-line TKI treatment. ctDNA detected the original mutations (OM) in 35/75 (48%) patients. Significantly higher detection rates were observed in TKI-naïve patients compared to the TKI-treated group, 70% versus 37%, respectively (p = 0.012). The detection of the original mutation at the study baseline was a negative predictor of progression-free survival (PFS) and overall survival (OS). The resistance mutation (T790M) was detected in 32/74 (43%) patients. In 27/32 (84%), the T790M was detected during treatment with TKI: in 25/27 patients, T790M was detected at the time of radiologic progression, in one patient, T790M was detected before radiologic progression, and in one patient, T790M was detected four weeks after starting systemic chemotherapy post progression on TKI. At the time of progression, the detection of T790M significantly correlates with the re-appearance of OM (p = 0.001). Conclusion: Plasma ctDNA is a noninvasive patient-friendly test that can be used to monitor response to treatment, early progression, and detection of acquired resistant mutations. Monitoring of clearance and re-emergence of driver mutations during TKI treatment effectively identifies progression of the disease. As larger NGS panels are available for ctDNA testing, these findings may also have implications for other biomarkers. The results from ongoing and prospective studies will further determine the utility of plasma testing to diagnose, monitor for disease progression, and guide treatment decisions in NSCLC.